Applying projectile motion model in determine of the maximum height in high jump / Syafiqah Hanis Mohd Fauzi - Mohd Fauzi, Syafiqah Hanis (2018)
High jump is a track and field event in which competition must jump unaided over a horizontal bar placed at measured heights without dislodging it. Every high jumper has a problem to jump high in order to clear the bar. Their coaches worry about this problem and want to improve their athletes’ performance. They need to know a few conditions that will affect the jump of their athletes’ and they can make a strategy to aimed maximum height in high jump. So, the purpose in this project is to determine the maximize jump height in high jump. In this project, method that will be use is projectile motion, which from physic and calculus. The present study, the result will obtain the maximum of approach horizontal velocity, the impact force due to the athletes’ mass and the effectiveness of time taken with the vertical distance. Hence, this research will help the athletes of the high jump to improve their high jump performance.